Influencia de varias tecnologías sobre la propagación intensiva del plátano en cámara térmica - Pinargote Zambrano, Gema Marcela (2021)
The objective of the research was to evaluate the influence of various technologies on the intensive propagation of plantain in a thermal chamber. The research was established in the Agricultural Research, Innovation and Development City (CIIDEA), at ESPAM MFL. Banana corms of the Dominico variety were used as propagation material. The experiment was developed with a randomized complete block design with 11 treatments, three replicates and 33 experimental units. The propagation treatments were combinations of propagation environments (thermal cameras covered with transparent plastic, black plastic and transparent plastic + light at night), corm sizes (corms between 500 - 500 g, 1000 - 1500 g, 1500 - 2000 g), substrates (rice husk, rice husk with river sand, rice husk with river sand and humus) and R1 shoot sizes to induce multi-buds (R1 shoots 5, 10 and 15 cm high). The main variables recorded were the multiplication rate of corms and per m2 of thermal camera surface. The data analysis was done with analysis of variance, the separation of means with Tukey at 5% probability of error. The optimal combination of propagation was obtained through regular analysis of Taguchi L9 (3) 4. The results based on the Taguchi maximum response prediction showed that the highest multiplication rate per corm was achieved with the combination of black plastic, corms between 1500 - 2000 g, substrates composed of rice husk, river sand and humus, and R1 shoot sizes for the induction of 15 cm high multi-buds, with which an average of 18 seedlings per corm was reached. The highest seedling multiplication rate per m2 was achieved with the combination of black plastic, corm size between 1000 - 1500 g, substrates composed of rice husk and river sand, and R1 shoot sizes for the induction of multi-buds 5 cm high, with which 260 seedlings were produced per m2 of thermal chamber. Keywords: Musa, Seedling proliferation, Growth chamber